Immune thrombocytopenic purpura in multiple sclerosis (clinical cases) - K. Z. Bakhtiyarova; T. D. Yunusov; O. V. Lyutov; U. Sh. Kuzmina (Neurology, Neuropsychiatry, Psychosomatics, 2026)
Immune thrombocytopenia (idiopathic thrombocytopenic purpura, ITP) and multiple sclerosis (MS) are two autoimmune diseases (AIDs), and their co-occurrence in a single patient is a rare combination. In recent years, there has been an increase in the prevalence of MS, as well as other AIDs; consequently, comorbid autoimmune conditions in individuals with MS are being observed with increasing frequency and are taking on significant scientific and clinical importance. Managing such patients is particularly challenging, as there is currently no established treatment strategy for patients with MS and concomitant ITP. The scientific literature describes isolated cases of the combination of MS and autoimmune thrombocytopenia, which may indicate shared pathogenetic mechanisms underlying these diseases. This article presents clinical cases illustrating two types of relationship between ITP and MS: primary autoimmune comorbidity of the conditions and secondary druginduced ITP. The widespread use in recent years of disease-modifying drugs (DMDs) and the planned expansion of their spectrum necessitate the stratification of the risks associated with this therapy.